Experiment-Based Learning in Elementary Science: A Descriptive Study of Fourth-Grade Students’ Learning Outcomes at SD 032 Matiti I - Grace Rawaty Manalu; Medianti Simanjuntak (Jurnal Pendidikan: Media, Strategi, dan Metode, 2025)
Science learning in elementary school should provide students with direct learning experiences that enable them to observe, investigate, discuss, and construct understanding from real phenomena. However, science instruction is still often dominated by teacher-centered explanation, which may limit students’ participation and conceptual understanding. This study aims to analyze fourth-grade students’ learning outcomes in science after the implementation of experiment-based learning at SD 032 Matiti I. This study employed a descriptive qualitative design supported by descriptive analysis of student score documentation. The participants were 34 fourth-grade students and one classroom teacher. Data were collected through classroom observation, semi-structured interviews, documentation, and analysis of students’ learning scores. The findings show that experiment-based learning supported students’ conceptual understanding, participation, curiosity, and enthusiasm during science learning. The average student score reached 79.35, which was categorized as high based on the learning outcome classification used in the study. Observation also showed that students were actively involved in visual, oral, mental, and emotional learning activities during the experiment-based lesson. Supporting factors included students’ preference for concrete activities, the flexibility of the Merdeka Curriculum, and teacher creativity in using simple materials from the surrounding environment. The main obstacles were limited science facilities, large class size, and differences in students’ levels of understanding. This study concludes that experiment-based learning is a relevant instructional method for improving the quality of elementary science learning, especially in schools with limited resources.